EFFECTIVENESS OF INCREASING MOVEMENT ACTIVITY USING PHYSICAL EDUCATION TOOLS IN PROFESSIONAL ACTIVITY - Allamuratov Sh.I.; Uraimov S.R. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article is intended to provide methodological support in the activities of enterprises, organizations and institutions to increase the labor efficiency of the population and prolong the labor activity.